Factors of the development of organic farming in Poland at the voivodship level - Nowak, Ewa; Jadczyszyn, Jan (Polish Journal of Agronomy, 2020)
The purpose of the research based on the data from the Report on the state of organic farming in Poland in 2015–2016 and environmental conditions, was to determine the impact of natural and economic factors and subsidies from EU programs on the level of organic production and to better understand the diver-sity of the spatial structure of organic farming within the system of provinces (voivodships). Nineteen structural, socio-economic and financial features, and 3 environmental features that charac-terize the quality of agricultural production and forms of nature protection for 16 voivodships, were used as assessment criteria.Principal component analysis allowed the basic factors of diver-sification to be discovered of the set of voivodships contained in the hidden structure defined by the features adopted for analysis. Homogeneous groups – organic farming types by voivodships were distinguished using the k-means method.The comparative analysis allowed the connections between the structure of organic farming and its place in voivodships to be highlighted in connection with support for organic farming, the number of producers of organic agricultural products, production of feed on arable land, production of cereals and vegetables. The location of organic farms is related to the occurrence of Natura 2000 areas. The first type includes two voivodships, Zachodnio-pomorskie and Warmińsko-Mazurskie – with the highest level of development of organic farming. In the second type, the fol-lowing voivodships were concentrated: Lubelskie, Łódzkie, Ma-zowieckie, Podlaskie and Świętokrzyskie, with a high level of or-ganic farming, where farms smaller in area, that focus on fruit and vegetable production are the predominant type. In the third type, the following voivodships were located in the region of western Poland: Pomorskie and Wielkopolskie with a medium level of organic farming and very diverse in characteristics, including the largest and smaller organic farms with a low level of fruit and vegetable production. The fourth type includes the Małopolskie and Podkarpackie voivodships with a very small farm area and a small number of producers. In the fifth type with the least developed organic farming with a small number of producers and low fruit and vegetable production, three voivodships focused on the average farm area: Śląskie, Opolskie and Kujawsko-Pomorskie.